Structures of Enterovirus 71 3C proteinase (strain E2004104‐TW‐CDC) and its complex with rupintrivir. (1st May 2013) - Wu, Caiming; Cai, Qixu; Chen, Chen; Li, Ning; Peng, Xuanjia; Cai, Yaxian; Yin, Ke; Chen, Xinsheng; Wang, Xiaolong; Zhang, Rongfu; Liu, Lijie; Chen, Shuhui; et al.
Abstract : The crystal structure of 3C proteinase (3C pro ) from Enterovirus 71 (EV71) was determined in space group C 2221 to 2.2 Å resolution. The fold was similar to that of 3C pro from other picornaviruses, but the difference in the β‐ribbon reported in a previous structure was not observed. This β‐ribbon was folded over the substrate‐binding cleft and constituted part of the essential binding sites for interaction with the substrate. The structure of its complex with rupintrivir (AG7088), a peptidomimetic inhibitor, was also characterized in space group P 21 21 21 to 1.96 Å resolution. The inhibitor was accommodated without any spatial hindrance despite the more constricted binding site; this was confirmed by functional assays, in which the inhibitor showed comparable potency towards EV71 3C pro and human rhinovirus 3C pro, which is the target that rupintrivir was designed against.